A Systematic Review of Non-pharmacological Strategies to Reduce the Risk of Violence in Patients With Schizophrenia Spectrum Disorders in Forensic Settings - Slamanig, Rudolf; Reisegger, Andreas; Winkler, Hildegard; de Girolamo, Giovanni; Carrà, Giuseppe; Crocamo, Cristina; Fangerau, Heiner; Markiewicz, Inga; Heitzman, Janusz; Salize, Hans Joachim; Picchioni, Marco; Wancata, Johannes (Frontiers in Psychiatry, 2021)
Background: The purpose of this systematic review is to systematically investigate which non-pharmacological interventions are effective in reducing violence risk among patients with schizophrenia spectrum disorders (SSD) in forensic settings. Methods: Six electronic data bases were searched. Two researchers independently screened 6,003 abstracts resulting in 143 potential papers. These were analyzed in detail by two independent researchers yielding 11 articles that could be used. Results: Of the 11 articles, four were non-randomized controlled trials, four were pre-post studies without controls, and one was observational. Only two studies applied a randomized controlled trial design. Cognitive behavioral treatment programs were investigated in four studies. A broad range of other interventions were studied. Often outcome measures were specific to each study and sample sizes were small. Frequently, important methodological information was missing from the papers. Due to the heterogeneity of the study designs and outcome measures meta-analysis could not be used. Conclusion: Due to methodological limitations it is difficult to draw firm conclusions about the effectiveness of non-pharmacological interventions to reduce the risk of violence in patents with SSD in forensic psychiatry settings. Studies applying better methods in terms of study design, sample sizes and outcome measures are urgently needed.